Ten Krishi Vigyan Kendras (agriculture extension offices) in two Indian States are setting up Farming System for Nutrition (FSN) models - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
The 2017 feasibility study in Wardha district, Maharashtra, India showed evidence of improvement in dietary diversity. Since then farmers from another 16 villages have been motivated to practise similar interventions. This grassroots-level uptake was a result of face-to-face engagement with farmers, demonstrations, and exposure visits to build capacity.